Posterior short segment spinal fixation in unstable fractures of the thoraco lumbar spine: radiological and neurological outcome assessment - S., Saju; Jacob, Tigy Thomas (International Journal of Research in Orthopaedics, 2019)
Background: A major dilemma still exists regarding management of unstable fractures of thoraco lumbar region. A posterior short segment spinal fixation without bone grafting improves spinal alignment, early ambulation and subsequent decrease in complications arising out of prolonged bedrest. Methods: A total of 30 patients presenting at the Accident and Emergency Department meeting the inclusion criteria were recruited for the study. A complete neurological and radiological assessment was done preoperatively, immediate post operatively and after 6 months using Frenkels grade system and Denis pain scale and Denis work scale respectively. Results: A statistically significant difference was observed between the initial kyphosis of the injured vertebra as compared to immediate postoperative period (p<0.0001), Improvement in neurological status was statistically significant at 6 month follow up (Z=4.355, p=0.00). Functional assessment revealed that 47% of the subjects experienced a minimal pain with a mean pain score of 1.9 with a mean functional score of 3.83 at the final follow up. Conclusions: Our study shows that short segment spinal fixation in unstable fractures of the thoraco lumbar spine provides a comparable neurological and functional outcome and is a reliable management option.